The effect of antibiotics on the periodontal treatment of diabetic patients with periodontitis: A systematic review and meta-analysis - Tang, Ziwei; Fan, Qi; Jiang, Qingsong; Li, Xiaolong; Wang, Yan; Long, Hu; Lai, Wenli; Jian, Fan (Frontiers in Pharmacology, 2023)
Background: To compare the effects of adjunctive antibiotic and mechanical treatment of periodontal disease with mechanical treatment alone on periodontal status and blood glucose levels in diabetic patients with periodontitis. Methods: Two independent reviewers (ZT and FJ) screened the PubMed database. Thirteen RCTs were included according to inclusion and exclusion criteria. To evaluate whether antibiotic-assisted periodontal therapy can improve periodontal status and blood glucose levels in diabetic patients with periodontitis. Reviewers independently performed data screening, data selection, data extraction, and risk of bias. Quality assessment of all selected randomized controlled trials was performed according to the Cochrane Handbook for Systematic Reviews of Interventions. Weighted mean differences and 95% confidence intervals (CIs) for continuous outcomes were calculated using random or fixed-effects models. This review is registered in the PROSPERO database (CRD42022347803). Results: Of the 13 included articles, 8 were on the use of systemic antibiotics and 5 on the use of topical antibiotics. The results showed no statistically significant improvement in periodontal status (probing depth, clinical attachment loss and bleeding on probing) at 3 months with adjuvant systemic antibiotics. However, there was a statistically significant improvement in periodontal status at 6 months (PD-6M P=0.04, BOP-6M P<0.0001, CAL-6M P=0.002). The improvement in PD with topical antibiotics was statistically significant at 1 month (P=0.0006). Conclusion: Antibiotics can improve the periodontal condition of diabetic patients with periodontitis to a certain extent. In clinical practice, it is necessary to comprehensively consider the balance of benefits and risks before deciding whether to use antibiotics.